Cover Picture: One Model, Two Enzymes: Activation of Hydrogen and Carbon Monoxide (Angew. Chem. Int. Ed. 33/2017). Issue 33 (21st June 2017) - Ogo, Seiji; Mori, Yuki; Ando, Tatsuya; Matsumoto, Takahiro; Yatabe, Takeshi; Yoon, Ki‐Seok; Hayashi, Hideki; Asano, Masashi
Abstract : A [NiIr]‐based catalyst turns the table on CO poisoning by exploiting the gas as a fuel. The system is able to act as a H2 oxidizing catalyst at low pH and as a CO oxidizing catalyst at high pH. At pH 7, there is a crossover where both oxidations are catalyzed simultaneously. In their Communication onpage 9723 ff., S. Ogo et al. report a proof‐of‐concept fuel cell that functioned on a 50:50 supply of H2 and CO. The double function is depicted above as a two‐headed bird.